5.10.3 Problems 201 to 300

Table 5.777: System of differential equations

#

ODE

Mathematica

Maple

1439

\[ {}[x_{1}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-5 x_{2} \left (t \right )+\csc \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-2 x_{2} \left (t \right )+\sec \left (t \right )] \]

1440

\[ {}\left [x_{1}^{\prime }\left (t \right ) = -\frac {x_{1} \left (t \right )}{2}-\frac {x_{2} \left (t \right )}{8}+\frac {{\mathrm e}^{-\frac {t}{2}}}{2}, x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-\frac {x_{2} \left (t \right )}{2}\right ] \]

1441

\[ {}[x_{1}^{\prime }\left (t \right ) = -2 x_{1} \left (t \right )+x_{2} \left (t \right )+2 \,{\mathrm e}^{-t}, x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-2 x_{2} \left (t \right )+3 t] \]

1442

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )-2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-2 x_{2} \left (t \right )] \]

1443

\[ {}[x_{1}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )-x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+x_{2} \left (t \right )] \]

1444

\[ {}[x_{1}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )-2 x_{2} \left (t \right )] \]

1445

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )-4 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )-7 x_{2} \left (t \right )] \]

1446

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )-5 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-3 x_{2} \left (t \right )] \]

1447

\[ {}[x_{1}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-5 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-2 x_{2} \left (t \right )] \]

1448

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )-2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )-x_{2} \left (t \right )] \]

1449

\[ {}\left [x_{1}^{\prime }\left (t \right ) = -x_{1} \left (t \right )-x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -\frac {5 x_{2} \left (t \right )}{2}\right ] \]

1450

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )-4 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-x_{2} \left (t \right )] \]

1451

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )+2 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -5 x_{1} \left (t \right )] \]

1452

\[ {}[x_{1}^{\prime }\left (t \right ) = -x_{1} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -x_{2} \left (t \right )] \]

1453

\[ {}\left [x_{1}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-\frac {5 x_{2} \left (t \right )}{2}, x_{2}^{\prime }\left (t \right ) = \frac {9 x_{1} \left (t \right )}{5}-x_{2} \left (t \right )\right ] \]

1454

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )+x_{2} \left (t \right )-2, x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-x_{2} \left (t \right )] \]

1455

\[ {}[x_{1}^{\prime }\left (t \right ) = -2 x_{1} \left (t \right )+x_{2} \left (t \right )-2, x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )-2 x_{2} \left (t \right )+1] \]

1456

\[ {}[x_{1}^{\prime }\left (t \right ) = -x_{1} \left (t \right )-x_{2} \left (t \right )-1, x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )-x_{2} \left (t \right )+5] \]

1457

\[ {}[x^{\prime }\left (t \right ) = -x \left (t \right ), y^{\prime }\left (t \right ) = -2 y \left (t \right )] \]

1458

\[ {}[x^{\prime }\left (t \right ) = -x \left (t \right ), y^{\prime }\left (t \right ) = 2 y \left (t \right )] \]

1459

\[ {}[x^{\prime }\left (t \right ) = -x \left (t \right ), y^{\prime }\left (t \right ) = 2 y \left (t \right )] \]

1460

\[ {}[x^{\prime }\left (t \right ) = -y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )] \]

1461

\[ {}[x^{\prime }\left (t \right ) = -y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )] \]

2239

\[ {}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )+2 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+y_{2} \left (t \right )] \]

2240

\[ {}\left [y_{1}^{\prime }\left (t \right ) = -\frac {5 y_{1} \left (t \right )}{4}+\frac {3 y_{2} \left (t \right )}{4}, y_{2}^{\prime }\left (t \right ) = \frac {3 y_{1} \left (t \right )}{4}-\frac {5 y_{2} \left (t \right )}{4}\right ] \]

2241

\[ {}\left [y_{1}^{\prime }\left (t \right ) = -\frac {4 y_{1} \left (t \right )}{5}+\frac {3 y_{2} \left (t \right )}{5}, y_{2}^{\prime }\left (t \right ) = -\frac {2 y_{1} \left (t \right )}{5}-\frac {11 y_{2} \left (t \right )}{5}\right ] \]

2242

\[ {}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )] \]

2243

\[ {}[y_{1}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )] \]

2244

\[ {}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-3 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )] \]

2245

\[ {}[y_{1}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )-3 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-2 y_{2} \left (t \right )] \]

2246

\[ {}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-2 y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+y_{2} \left (t \right )-y_{3} \left (t \right )] \]

2247

\[ {}[y_{1}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )-4 y_{2} \left (t \right )-8 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )-4 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -8 y_{1} \left (t \right )-4 y_{2} \left (t \right )-6 y_{3} \left (t \right )] \]

2248

\[ {}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+5 y_{2} \left (t \right )+8 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )-y_{3} \left (t \right )] \]

2249

\[ {}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )+2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 12 y_{1} \left (t \right )-4 y_{2} \left (t \right )+10 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )+y_{2} \left (t \right )-7 y_{3} \left (t \right )] \]

2250

\[ {}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-y_{2} \left (t \right )-4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-3 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )-y_{3} \left (t \right )] \]

2251

\[ {}[y_{1}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{2} \left (t \right )-6 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+6 y_{2} \left (t \right )+2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )-2 y_{2} \left (t \right )+2 y_{3} \left (t \right )] \]

2252

\[ {}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+2 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+7 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -10 y_{1} \left (t \right )+10 y_{2} \left (t \right )-5 y_{3} \left (t \right )] \]

2253

\[ {}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+y_{2} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+5 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )+2 y_{2} \left (t \right )+4 y_{3} \left (t \right )] \]

2254

\[ {}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+7 y_{2} \left (t \right )] \]

2255

\[ {}[y_{1}^{\prime }\left (t \right ) = -y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-2 y_{2} \left (t \right )] \]

2256

\[ {}[y_{1}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )+4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-11 y_{2} \left (t \right )] \]

2257

\[ {}[y_{1}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+y_{2} \left (t \right )] \]

2258

\[ {}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )+12 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-8 y_{2} \left (t \right )] \]

2259

\[ {}[y_{1}^{\prime }\left (t \right ) = -10 y_{1} \left (t \right )+9 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+2 y_{2} \left (t \right )] \]

2260

\[ {}[y_{1}^{\prime }\left (t \right ) = -13 y_{1} \left (t \right )+16 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -9 y_{1} \left (t \right )+11 y_{2} \left (t \right )] \]

2261

\[ {}[y_{1}^{\prime }\left (t \right ) = 2 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+6 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 4 y_{2} \left (t \right )+2 y_{3} \left (t \right )] \]

2262

\[ {}\left [y_{1}^{\prime }\left (t \right ) = \frac {y_{1} \left (t \right )}{3}+\frac {y_{2} \left (t \right )}{3}-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -\frac {4 y_{1} \left (t \right )}{3}-\frac {4 y_{2} \left (t \right )}{3}+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -\frac {2 y_{1} \left (t \right )}{3}+\frac {y_{2} \left (t \right )}{3}\right ] \]

2263

\[ {}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+y_{2} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+3 y_{2} \left (t \right )-y_{3} \left (t \right )] \]

2264

\[ {}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-2 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+3 y_{2} \left (t \right )-y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )+3 y_{3} \left (t \right )] \]

2265

\[ {}[y_{1}^{\prime }\left (t \right ) = 6 y_{1} \left (t \right )-5 y_{2} \left (t \right )+3 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )+3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+y_{2} \left (t \right )+y_{3} \left (t \right )] \]

2266

\[ {}[y_{1}^{\prime }\left (t \right ) = -11 y_{1} \left (t \right )+8 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )-3 y_{2} \left (t \right )] \]

2267

\[ {}[y_{1}^{\prime }\left (t \right ) = 15 y_{1} \left (t \right )-9 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 16 y_{1} \left (t \right )-9 y_{2} \left (t \right )] \]

2268

\[ {}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-7 y_{2} \left (t \right )] \]

2269

\[ {}[y_{1}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )+24 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )+17 y_{2} \left (t \right )] \]

2270

\[ {}[y_{1}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )+3 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-y_{2} \left (t \right )] \]

2271

\[ {}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )-y_{3} \left (t \right )] \]

2272

\[ {}[y_{1}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )+3 y_{2} \left (t \right )+2 y_{3} \left (t \right )] \]

2273

\[ {}[y_{1}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )-4 y_{2} \left (t \right )+4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -9 y_{1} \left (t \right )-5 y_{2} \left (t \right )+6 y_{3} \left (t \right )] \]

2274

\[ {}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-4 y_{2} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )+6 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-2 y_{2} \left (t \right )+3 y_{3} \left (t \right )] \]

2275

\[ {}[y_{1}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-8 y_{2} \left (t \right )-4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-y_{2} \left (t \right )-4 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right )+9 y_{3} \left (t \right )] \]

2276

\[ {}[y_{1}^{\prime }\left (t \right ) = -5 y_{1} \left (t \right )-y_{2} \left (t \right )+11 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -7 y_{1} \left (t \right )+y_{2} \left (t \right )+13 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+8 y_{3} \left (t \right )] \]

2277

\[ {}[y_{1}^{\prime }\left (t \right ) = 5 y_{1} \left (t \right )-y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+9 y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )+2 y_{2} \left (t \right )+4 y_{3} \left (t \right )] \]

2278

\[ {}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )+10 y_{2} \left (t \right )-12 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+2 y_{2} \left (t \right )+3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )+6 y_{3} \left (t \right )] \]

2279

\[ {}[y_{1}^{\prime }\left (t \right ) = -6 y_{1} \left (t \right )-4 y_{2} \left (t \right )-4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+3 y_{2} \left (t \right )+y_{3} \left (t \right )] \]

2280

\[ {}[y_{1}^{\prime }\left (t \right ) = 2 y_{2} \left (t \right )-2 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+5 y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )+y_{2} \left (t \right )+y_{3} \left (t \right )] \]

2281

\[ {}[y_{1}^{\prime }\left (t \right ) = -2 y_{1} \left (t \right )-12 y_{2} \left (t \right )+10 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-24 y_{2} \left (t \right )+11 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )-24 y_{2} \left (t \right )+8 y_{3} \left (t \right )] \]

2282

\[ {}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-12 y_{2} \left (t \right )+8 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-9 y_{2} \left (t \right )+4 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )-6 y_{2} \left (t \right )+y_{3} \left (t \right )] \]

2283

\[ {}[y_{1}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-3 y_{2} \left (t \right )-y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )-2 y_{3} \left (t \right )] \]

2284

\[ {}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-3 y_{2} \left (t \right )+4 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )+5 y_{2} \left (t \right )-8 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+3 y_{2} \left (t \right )-5 y_{3} \left (t \right )] \]

2285

\[ {}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-y_{2} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -y_{1} \left (t \right )-y_{2} \left (t \right )-2 y_{3} \left (t \right )] \]

2286

\[ {}[y_{1}^{\prime }\left (t \right ) = -y_{1} \left (t \right )+2 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -5 y_{1} \left (t \right )+5 y_{2} \left (t \right )] \]

2287

\[ {}[y_{1}^{\prime }\left (t \right ) = -11 y_{1} \left (t \right )+4 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -26 y_{1} \left (t \right )+9 y_{2} \left (t \right )] \]

2288

\[ {}[y_{1}^{\prime }\left (t \right ) = y_{1} \left (t \right )+2 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = -4 y_{1} \left (t \right )+5 y_{2} \left (t \right )] \]

2289

\[ {}[y_{1}^{\prime }\left (t \right ) = 5 y_{1} \left (t \right )-6 y_{2} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 3 y_{1} \left (t \right )-y_{2} \left (t \right )] \]

2290

\[ {}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )-3 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 2 y_{2} \left (t \right )+2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 5 y_{1} \left (t \right )+y_{2} \left (t \right )+y_{3} \left (t \right )] \]

2291

\[ {}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )+3 y_{2} \left (t \right )+y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{1} \left (t \right )-5 y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )+7 y_{2} \left (t \right )+3 y_{3} \left (t \right )] \]

2292

\[ {}[y_{1}^{\prime }\left (t \right ) = 2 y_{1} \left (t \right )+y_{2} \left (t \right )-y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = y_{2} \left (t \right )+y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = y_{1} \left (t \right )+y_{3} \left (t \right )] \]

2293

\[ {}[y_{1}^{\prime }\left (t \right ) = -3 y_{1} \left (t \right )+y_{2} \left (t \right )-3 y_{3} \left (t \right ), y_{2}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-y_{2} \left (t \right )+2 y_{3} \left (t \right ), y_{3}^{\prime }\left (t \right ) = 4 y_{1} \left (t \right )-2 y_{2} \left (t \right )+3 y_{3} \left (t \right )] \]

2698

\[ {}[x^{\prime }\left (t \right ) = 6 x \left (t \right )-3 y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+y \left (t \right )] \]

2699

\[ {}[x^{\prime }\left (t \right ) = -2 x \left (t \right )+y \left (t \right )+t, y^{\prime }\left (t \right ) = -4 x \left (t \right )+3 y \left (t \right )-1] \]

2700

\[ {}[x^{\prime }\left (t \right ) = 6 x \left (t \right )-3 y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+y \left (t \right )] \]

2701

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right )+y \left (t \right )+{\mathrm e}^{t}, y^{\prime }\left (t \right ) = x \left (t \right )-y \left (t \right )-{\mathrm e}^{t}] \]

2702

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right )+y \left (t \right ), y^{\prime }\left (t \right ) = 4 x \left (t \right )+y \left (t \right )] \]

2703

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right )-3 y \left (t \right ), y^{\prime }\left (t \right ) = -2 x \left (t \right )+2 y \left (t \right )] \]

2704

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right )-y \left (t \right ), y^{\prime }\left (t \right ) = 5 x \left (t \right )-3 y \left (t \right )] \]

2705

\[ {}[x^{\prime }\left (t \right ) = 3 x \left (t \right )-2 y \left (t \right ), y^{\prime }\left (t \right ) = 4 x \left (t \right )-y \left (t \right )] \]

2706

\[ {}[x^{\prime }\left (t \right ) = 4 x \left (t \right )+5 y \left (t \right )+4 \,{\mathrm e}^{t} \cos \left (t \right ), y^{\prime }\left (t \right ) = -2 x \left (t \right )-2 y \left (t \right )] \]

2707

\[ {}[x^{\prime }\left (t \right ) = 3 x \left (t \right )-4 y \left (t \right )+{\mathrm e}^{t}, y^{\prime }\left (t \right ) = x \left (t \right )-y \left (t \right )+{\mathrm e}^{t}] \]

2708

\[ {}[x^{\prime }\left (t \right ) = 2 x \left (t \right )-5 y \left (t \right )+\sin \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )-2 y \left (t \right )+\tan \left (t \right )] \]

2709

\[ {}[x^{\prime }\left (t \right ) = y \left (t \right )+\textit {f\_1} \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )+f_{2} \left (t \right )] \]

2728

\[ {}[x_{1}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )-3 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+x_{2} \left (t \right )] \]

2729

\[ {}[x_{1}^{\prime }\left (t \right ) = -2 x_{1} \left (t \right )+x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -4 x_{1} \left (t \right )+3 x_{2} \left (t \right )] \]

2730

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+2 x_{2} \left (t \right )+4 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 2 x_{1} \left (t \right )+2 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+2 x_{2} \left (t \right )+3 x_{3} \left (t \right )] \]

2731

\[ {}[x_{1}^{\prime }\left (t \right ) = 7 x_{1} \left (t \right )-x_{2} \left (t \right )+6 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -10 x_{1} \left (t \right )+4 x_{2} \left (t \right )-12 x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = -2 x_{1} \left (t \right )+x_{2} \left (t \right )-x_{3} \left (t \right )] \]

2732

\[ {}[x_{1}^{\prime }\left (t \right ) = -7 x_{1} \left (t \right )+6 x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 5 x_{2} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 6 x_{1} \left (t \right )+2 x_{3} \left (t \right )] \]

2733

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )+2 x_{2} \left (t \right )+3 x_{3} \left (t \right )+6 x_{4} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+6 x_{2} \left (t \right )+9 x_{3} \left (t \right )+18 x_{4} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 5 x_{1} \left (t \right )+10 x_{2} \left (t \right )+15 x_{3} \left (t \right )+30 x_{4} \left (t \right ), x_{4}^{\prime }\left (t \right ) = 7 x_{1} \left (t \right )+14 x_{2} \left (t \right )+21 x_{3} \left (t \right )+42 x_{4} \left (t \right )] \]

2734

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )+x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = 4 x_{1} \left (t \right )+x_{2} \left (t \right )] \]

2735

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )-3 x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = -2 x_{1} \left (t \right )+2 x_{2} \left (t \right )] \]

2736

\[ {}[x_{1}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+x_{2} \left (t \right )-x_{3} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )+3 x_{2} \left (t \right )-x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = 3 x_{1} \left (t \right )+3 x_{2} \left (t \right )-x_{3} \left (t \right )] \]

2737

\[ {}[x_{1}^{\prime }\left (t \right ) = x_{1} \left (t \right )-x_{2} \left (t \right ), x_{2}^{\prime }\left (t \right ) = x_{1} \left (t \right )+2 x_{2} \left (t \right )+x_{3} \left (t \right ), x_{3}^{\prime }\left (t \right ) = x_{1} \left (t \right )+10 x_{2} \left (t \right )+2 x_{3} \left (t \right )] \]